The Research on Color Grading of Green Jade Images Based on HSL Chromaticity Analysis - Zhang Lili; Yuan Xinqiang (MATEC Web of Conferences, 2016)
This study aims to establish a simple and convenient method suitable for the market to grade the jade colors. Based on the HSL color model and with the assistance of the HSL analysis on green jade images acquired by camera flashlights, this study obtains the following six kinds of jade colors: melon green, emerald green, yellow green, bean green, light bean green, and light green, based on which the law governing the values and the value range can be determined, and the respective HSL value ranges ,together with their threshold values, for the seven green jades can be finally found, thus laying an important foundation for further researches on computer-based quick grading. It is also hoped that this method will be widely applied and promoted in the marketplace and realizes our ultimate goal of setting guidelines to commercial jade prices.